The impact of banking sector competition on access to finance: the case of selected African countries - Landani, Namhla (My University, 2022)
The impact of banking competition and access to finance is still the subject of debate amongst scholars, with some inferring the information hypothesis and others the market power hypothesis. This study investigates the consequences of bank competition on access to finance using data primarily from the World Bank’s Enterprise Surveys for 33 African countries. The study computes country-level access to finance variables and uses three New Empirical Industrial Organisation measures (Boone indicator, H-statistics and Lerner index) for a crosssectional and panel dataset. The results of the analysis are consistent with the information hypothesis as both the Lerner index and Boone indicator infer a positive relationship between concentration and access to finance in the long-run panel results. Although the H-statistic is positively related to access to finance, its low marginal effects indicate low transmission of input prices on African firms’ revenue, alluding to the information hypothesis. African economies therefore need to improve information sharing by supporting businesses to maintain detailed records of financial information, and there needs to be more bank development for more cost effective collation of data during the lending process. Inducing more competition is also useful in reducing interest rates for better access to finance. Furthermore, the study finds that African countries that are experiencing growth in their GDP improve access to finance, and it is not countries with high GDP that have higher access to finance.
A research report submitted in partial fulfilment of the Degree of Master of Commerce in Economics to the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2022